3(y-9)=-4(-2y+3)

Simple and best practice solution for 3(y-9)=-4(-2y+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-9)=-4(-2y+3) equation:



3(y-9)=-4(-2y+3)
We move all terms to the left:
3(y-9)-(-4(-2y+3))=0
We multiply parentheses
3y-(-4(-2y+3))-27=0
We calculate terms in parentheses: -(-4(-2y+3)), so:
-4(-2y+3)
We multiply parentheses
8y-12
Back to the equation:
-(8y-12)
We get rid of parentheses
3y-8y+12-27=0
We add all the numbers together, and all the variables
-5y-15=0
We move all terms containing y to the left, all other terms to the right
-5y=15
y=15/-5
y=-3

See similar equations:

| (25/16)^x=4/5 | | 1/2n-8=7 | | 3c-3c=14 | | 7•23/y=191/4 | | 2x+62+82+40=180 | | -n-1n-6=21 | | 2s-6s+5s=33 | | 25/16=4/5^x | | 2x+3x+3x+4x=72 | | 15-7(5+6)=a | | 720=x+4.0x10^3x | | 3.1y=6.6 | | 18/3=x/8 | | 9(x-5)=3(3x+15) | | 2(4a-1)-7a=9-4 | | P-9=-7p+7 | | X²-5x-36=0 | | 3n-11=64 | | 20=(3/4)x-4 | | 2p+3p=5p | | 9/15=5x+1/3x+23 | | 9x-40=-11 | | 9^2x+3=1/27^3x+1 | | 3n^2+25n+28=0 | | 4/x-56=-56 | | 2+(-2x)=14 | | 6+5(8+4x)=-94 | | 9x-12=3+4x | | 5m^2-4m-24=0 | | 16(0)+13y=13 | | x/60=4/12 | | 22y=6 |

Equations solver categories